Rural Housing Rental Rates in China: Regional Differences, Influencing Factors, and Policy Implications - Li Huang; Minjie Zheng; Rongyu Wang (Land, 2022)
Through recognition and mastery of the regional differences and influencing factors of China’s rural housing rental rates, we can better understand changes in the functional attributes of homesteads and deepen the reform of “separating rural land ownership rights, contract rights, and management rights” of homesteads. Accordingly, this paper uses village residence data from the China Labor-force Dynamics Survey to measure the degree of regional differences in rural housing rental rates at the province level and empirically analyze the influencing factors with villages (residences) as measuring unit. The study yields four main findings. First, rural housing rental behavior exists to varying degrees in the vast majority of provinces nationwide. Second, according to the spatial distribution pattern, rural housing rental rates are generally high in the eastern coastal region and low in the central, western, and northeastern regions, mainly reflecting unique characteristics of the eastern region. Third, although the level of economic development is important, it is not the only factor explaining regional differences in rural housing rental rates. Fourth, rural housing rental rates are mainly influenced by a combination of three types of factors: physiographic, socioeconomic, and village governance factors. Among them, factors such as proximity to suburban areas, the proportion of non-local permanent residents, annual per capita income, and village infrastructure conditions have significant positive effects, whereas factors such as distance from administrative centers, reliance on funding from the higher-level authority of the village committee, and the degree of harmony between villages and cadres have significant negative effects. By interpreting the policy implications of these findings, we hope to provide a reference for localized, categorical reform of the homestead system.